Transformasi Digital pada UMKM Brownies Melalui Pengembangan Website Penjualan Online - Hanifah Permatasari; Aprilisa Arum Sari; KUSUMA HAAFIDZH MUNIR FAUZI (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in strengthening the community’s economy. However, many business owners still face difficulties in managing and marketing their products due to the limited use of digital technology. This community service activity aims to support the digital transformation of Kurnia Brownies through the development of a web-based sales information system. The implementation method includes identifying partner needs, designing and implementing the system, conducting training sessions, as well as providing mentoring and system handover. The developed system features product management, order transactions, customer management, and direct communication between customers and administrators through a chat feature. The results show that the system improves operational efficiency, expands marketing reach, and enhances the business’s professional image. The partner is able to manage online sales independently with the help of the provided training and user guide. This activity concludes that the application of information technology through an online sales website serves as an effective solution to strengthen competitiveness and promote digital independence among MSMEs in the technology-driven economy era.